Thyroidectomy for symptomatic goitre in a field hospital setting. a general surgeon’s experience in Malaysian field hospital, Cox’s Bazaar Bangladesh - Azzam, Wazir; Razak, Asma'; Mahno, Noor Ezmas; Karim, Khasnizal (Wiley-Blackwell, 2020)
Purpose: To describe the experience of thyroidectomy for symptomatic goitre in a Field Hospital setting. Methodology: All patients who underwent thyroidectomy for symptomatic goitre between 1st September 2018 to 20th February 2019 were included. Preoperative, intra-operative and post-operative data were taken.Thyroid function test (TFT) was done in a nearby NGO hospital and thyrotoxicosis was treated first prior to surgery. Prophylactic antibiotics was given with IV amoxycillin/clavulanate 1.2 g. Thyroidectomy was performed in a standard form using bipolar diathermy and sutures. Drain was inserted when indicated. Post operatively serum calcium and later TFT was measured. Results: A total of 19 patients had thyroidectomy. 7 patients had hemithyroidectomy and 12 patients had total thyroidectomy. 7 patients weretoxic goitres, 4 had huge goitre with retrosternal extension and 1 patient wasrhesus negative requiring autologous blood storage preoperatively. Decision for type of surgery was done on a case to case basis. All patients had compression symptoms. Cervical and chest X-rays were taken. Ultrasound was done by the Emergency Physician. Intraoperatively there were no complica-tions, mean blood loss was 20 ml, mean operating time was 104 minutes for total thyroidectomy and 56 minutes for hemithyroidectomy. Post-operatively 1 patient had transient hoarseness of voice for 2 months,3 patients had transient mild hypocalcemia and all patients had resolution of compression symptoms. Histopathological services was not available at that time. Conclusion: Thyroidectomy in a Field Hospital setting is a feasible option in areas of prolonged crisis